Viabilidade econômica do cultivo irrigado do cajueiro anão precoce na agricultura familiar - Macêdo, Marcelo Lima (2013)
The cashew (Anacardium occidentale L.) has always occupied a prominent place in Brazilian agriculture, especially in the Northeast, where it occupies an area of 760110 ha being its cultivation conducted under rain fed conditions, with low technology and low productivity. With the development by Embrapa of clone dwarfs, whose production favorably characterizs not only the cashew itself, but also the pseudo-fruit, envisions the possibility of irrigated cultivation of cashew, functioning as an alternative source of income for the family farmer. The objective of this study was to evaluate the economic viability of the irrigated dwarf cashew. The study was conducted in the municipality of Pentecost-CE based on the production of 1.0 ha cultivated with BRS 189, deployed in the area of family farming in the nucleus D the Irrigation Curu Pentecost. It was considered for analysis of production data for a period of ten through the indicators of profitability of investment analysis Regarding Benefit / Cost, Net Present Value, Internal Rate of Return and the period "Payback". Irrigation cashew promoted an increase in productivity of around 90%, although the harvest period practically did not change; There was a direct relationship between the total annual rainfall and productivity of cashew, regardless the culture, is under rain fed or irrigated; cultivation of dwarf cashew irrigated performed as an economically viable alternative in a scenario where the costs of labor associated with harvesting is not taken into account.